Recovery of Donor Meadows of Posidonia sinuosa and Posidonia australis Contributes to Sustainable Seagrass Transplantation. (27th October 2011) - Verduin, Jennifer J.; Paling, E. I.; van Keulen, M.; Rivers, Lotte E.
Abstract : Donor meadow recovery is important in deciding whether removal of material from natural seagrass meadows is a sustainable activity. Thus an investigation into meadow regrowth was undertaken as part of a large-scale seagrass rehabilitation effort in Cockburn Sound, Western Australia. Several plug extraction configurations were examined in Posidonia sinuosa and Posidonia australis meadows to monitor shoot growth into plug scars. No significant differences in shoot growth between extraction configurations were observed, and both species increased their shoot numbers over two years, with P. sinuosa showing a significantly better recovery rate than P. australis . P. sinuosa shoot recovery into extracted areas was2.2 ± 0.1 shoots over 24 months, similar to shoot changes in controls (2.3 shoots over the same period). P. australis shoot recovery for each configuration was 0.8 ± 0.3 shoots in 24 months compared with 1.5 shoots in the controls. Based on the number of regrowing shoots, the predicted recovery time of a meadow is estimated at 4 years for P. sinuosa and three years for P. australis . Different plug extraction configurations do not appear to affect meadow recovery, and it can be concluded that established meadows of both species are sustainable providers of planting units for rehabilitation measures.